Agricultura e proteção efetiva: uma análise parcial do caso brasileiro - Moraes, Nelson; Lima Bandeira, Antonio; Barbosa, Túlio (Revista Ceres, 2025)
The results of this study lead to the conclusion that the main agricultural activities oriented toward foreign trad were discriminated against by trade policies adopted during the period 1947-73.